2017
DOI: 10.1111/jam.13456
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of microbial community during ensiling direct-cut alfalfa with and without LAB inoculant and sugar

Abstract: High-throughput sequencing based on a novel Clostridia-specific primer set proved a potentially useful tool to study the clostridial community dynamics, and could aid to elucidate the mechanism by which the clostridial fermentation develops during the ensiling of alfalfa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
109
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 48 publications
(71 reference statements)
16
109
1
1
Order By: Relevance
“…Although richness of bacterial community decreased compared with the ensiling material at the early stage of ensiling, the richness ourished at 90 d. Similar trends were also reported by Zheng et al (2017) in direct-cut alfalfa silage with and without LAB inoculant and sugar and by Keshri et al (2018) in untreated corn silage, in which richness of the bacterial community decreased at the early stage of ensiling compared with the alfalfa material, and later increased during the ensiling process. Consistent with the study of Ni (2017a), diversity of the bacterial community decreased after ensiling.…”
Section: Effects Of L Plantarum On Bacterial Community Of Alfalfa Sisupporting
confidence: 80%
“…Although richness of bacterial community decreased compared with the ensiling material at the early stage of ensiling, the richness ourished at 90 d. Similar trends were also reported by Zheng et al (2017) in direct-cut alfalfa silage with and without LAB inoculant and sugar and by Keshri et al (2018) in untreated corn silage, in which richness of the bacterial community decreased at the early stage of ensiling compared with the alfalfa material, and later increased during the ensiling process. Consistent with the study of Ni (2017a), diversity of the bacterial community decreased after ensiling.…”
Section: Effects Of L Plantarum On Bacterial Community Of Alfalfa Sisupporting
confidence: 80%
“…Then, three PCR products were mixed in equi-density ratios. Finally, mixture was purified for DNA concentration and sequencing (Li et al 2015;Zheng et al 2017). Therefore, the data of high-throughput sequencing were not able to be further statistically analyzed.…”
Section: Analysis Of Microbial Diversity Through High-throughput Sequmentioning
confidence: 99%
“…Extensive studies have been conducted to disclose the most abundant microbial community in the chicken GIT by using culture-based approach, DNA fingerprinting method and polymerase chain reaction (PCR)-based sequencing (Xiao et al 2017). Although these studies have expanded our knowledge of the intestinal microbiota, they only identified a few of the most abundant operational taxonomic units (OTUs) present, because of their poor limits of detection (Zheng et al 2017).…”
Section: Introductionmentioning
confidence: 99%